LBJ - Reiner, Rob; Harrelson, Woody; Leigh, Jennifer Jason, 1962-; Pullman, Bill; Shaiman, Marc (Culver City, California : Sony Pictures Home Entertainment, 2018)
The story of Lyndon Baines Johnson, as he was thrust into office after the assassination of President John F. Kennedy in 1963.
Originally released as a motion picture in 2016.
Anamorphic wide screen 2.35:1.
New DVD Winter 2023.
Director of photography, Barry Markowitz ; production designer, Christopher R. DeMuri ; editor, Bob Joyce ; music, Marc Shaiman.
Woody Harrelson, Jennifer Jason Leigh, Bill Pullman, C. Thomas Howell, Jeffrey Donovan.
MPAA rating: R.
Keywords: Johnson, Lyndon B. -- 1908-1973 -- Drama; Presidents -- United States -- Drama; Video recordings for the hearing impaired; DVDs; Biographical films